2021
DOI: 10.1001/jamanetworkopen.2021.12076
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clinical Symptoms by Race Among Women With Early-Stage, Hormone Receptor–Positive Breast Cancer Before Starting Chemotherapy

Abstract: Key Points Question Are there symptom burden differences between Black and White women with early-stage breast cancer before starting chemotherapy? Findings In this cross-sectional observatonal study of 1338 patients from 1 cancer center, Black women reported a higher burden for symptoms typically associated with chemotherapy and lower distress than White women before chemotherapy intiation. Black patients’ baseline characteristics were associated with a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…Black women experience a higher symptom burden and more frequently face undertreatment of symptoms, such as pain. 11 , 12 , 13 , 14 , 15 , 16 Differences in socioeconomic status, higher rates of exposure to environmental risk factors, lower access to health care, and explicit and implicit clinician bias driven by centuries of racism, oppression, and disinvestment, rather than biological differences, contribute to higher symptom burden among Black women. 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 Race is a social construct, 23 and observed differences in health experiences and outcomes by marginalized groups must be understood in the broader context of structural racism and other factors that differentially place minorities at increased risks for high symptom burden, enduring disparities in treatment adherence, and breast cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Black women experience a higher symptom burden and more frequently face undertreatment of symptoms, such as pain. 11 , 12 , 13 , 14 , 15 , 16 Differences in socioeconomic status, higher rates of exposure to environmental risk factors, lower access to health care, and explicit and implicit clinician bias driven by centuries of racism, oppression, and disinvestment, rather than biological differences, contribute to higher symptom burden among Black women. 11 , 16 , 17 , 18 , 19 , 20 , 21 , 22 Race is a social construct, 23 and observed differences in health experiences and outcomes by marginalized groups must be understood in the broader context of structural racism and other factors that differentially place minorities at increased risks for high symptom burden, enduring disparities in treatment adherence, and breast cancer outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Black women experience a higher symptom burden and more frequently face undertreatment of symptoms, such as pain . Differences in socioeconomic status, higher rates of exposure to environmental risk factors, lower access to health care, and explicit and implicit clinician bias driven by centuries of racism, oppression, and disinvestment, rather than biological differences, contribute to higher symptom burden among Black women .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the black race experienced more side effects than the white race. 11 Cancer Related Fatigue (CRF) is a condition of fatigue caused by cancer or a side effect of cancer treatment. Approximately 80% to 90% of patients experience fatigue while undergoing chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Disparities in follow-up after screening and treatment have been observed for Asian, Black, and Hispanic women . Adjuvant endocrine therapy reduces the risk of cancer recurrence among individuals with hormonal receptor–positive cancers, but long-term adherence can be difficult.…”
Section: Practice Considerationsmentioning
confidence: 99%
“…Adjuvant endocrine therapy reduces the risk of cancer recurrence among individuals with hormonal receptor–positive cancers, but long-term adherence can be difficult. Black women are more likely to discontinue adjuvant endocrine therapy compared with White women, in part due to greater physical (vasomotor, musculoskeletal, or cardiorespiratory) and psychological (distress or despair) symptom burdens . Improvements in access to effective health care, removal of financial barriers, and use of support services to ensure equitable follow-up after screening and timely and effective treatment of breast cancer have the potential to reduce mortality for individuals experiencing disparities related to racism, rural location, low income, or other factors associated with lower breast cancer survival.…”
Section: Practice Considerationsmentioning
confidence: 99%